Development and validation of a prediction rule for early discharge of low-risk emergency department patients with potential ischemic chest pain. Issue 2 (4th March 2015) - Scheuermeyer, Frank Xavier; Wong, Hubert; Yu, Eugenia; Boychuk, Barb; Innes, Grant; Grafstein, Eric; Gin, Kenneth; Christenson, Jim
ABSTRACT: Objectives: Current guidelines emphasize that emergency department (ED) patients at low risk for potential ischemic chest pain cannot be discharged without extensive investigations or hospitalization to minimize the risk of missing acute coronary syndrome (ACS). We sought to derive and validate a prediction rule that permitted 20 to 30% of ED patients without ACS safely to be discharged within 2 hours without further provocative cardiac testing. Methods: This prospective cohort study enrolled 1, 669 chest pain patients in two blocks in 2000–2003 (development cohort) and 2006 (validation cohort). The primary outcome was 30-day ACS diagnosis. A recursive partitioning model incorporated reliable and predictive cardiac risk factors, pain characteristics, electrocardiographic findings, and cardiac biomarker results. Results: In the derivation cohort, 165 of 763 patients (21.6%) had a 30-day ACS diagnosis. The derived prediction rule was 100.0% sensitive and 18.6% specific. In the validation cohort, 119 of 906 patients (13.1%) had ACS, and the prediction rule was 99.2% sensitive (95% CI 95.4–100.0) and 23.4% specific (95% CI 20.6–26.5). Patients have a very low ACS risk if arrival and 2-hour troponin levels are normal, the initial electrocardiogram is nonischemic, there is no history of ACS or nitrate use, age is < 50 years, and defined pain characteristics are met. The validation of the rule was limited by the lack of consistency in data capture, incomplete follow-up, and lack of evaluation of the accuracy, comfort, and clinical sensibility of this clinical decision rule. Conclusion: The Vancouver Chest Pain Rule may identify a cohort of ED chest pain patients who can be safely discharged within 2 hours without provocative cardiac testing. Further validation across other centres with consistent application and comprehensive and uniform follow-up of all eligible and enrolled patients, in addition to measuring and reporting the accuracy of and comfort level with applying the rule and the clinical sensibility, should be completed prior to adoption and implementation.